Implementation of Islamic Education Values in the Formation of Student Character at MTs Manongkoki, Takalar Regency - Syafriwana, Syafriwana; Basri, Basri; Kamaruddin, Kamaruddin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to describe the implementation of Islamic educational values ​​in the formation of student character at MTs Manongkoki, Takalar Regency. The background of this study is the importance of the role of Islamic education in forming the personality and noble morals of students amidst the challenges of the ever-evolving era. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the values ​​of Islamic education applied at MTs Manongkoki include the values ​​of faith, honesty, responsibility, discipline, and social concern. The implementation of these values ​​is carried out through formal learning in the classroom, religious extracurricular activities, as well as the role models of teachers and a religious school environment. Supporting factors in the formation of student character are the active role of teachers, parental support, and school religious programs. Meanwhile, the obstacles faced include the influence of the environment outside the school and the lack of individual student discipline. This study concludes that the implementation of Islamic educational values ​​at MTs Manongkoki contributes significantly to forming the character of students who have noble and responsible morals.